Nondestructive and destructive evaluation of wood strength and its relation to cellular microstructure - Nurul Faziha, Ibrahim (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Non-destructive evaluation (NDE) of wood is a method of identifying wood quality without damaging the samples and its eliminate the tedious specimen preparation in order to determine the mechanical properties of wood. Wood properties can be determined rapidly by in situ inspection during its service life or measured directly from standing trees without reducing the economic value of its timber. This study assess the feasibility of free-free flexural vibration method, one of NDE techniques for estimating the wood stiffness of plantation species namely Acacia mangium, Hevea brasiliensis and Paraserianthes mOluccanaJ The specific objective of this study were (i) determine the dynamic modulus of elasticity (DMOE) on the three plantation species, (ii) establish the relationship between DMOE obtained from nondestructive and modulus of elasticity (MOE), modulus of rupture (MOR), Young's modulus (E) and maximum crushing strength (MCS) obtained from destructive test, (iii) evaluate the effects of tension wood on DMOE, MOE and MaR, and (iv) analyze the relationship between anatomical properties and mechanical properties. For this purpose, wood specimens with dimension 20 mm (T) x 10 mm (R) x 340 mm (L) were prepared for non-destructive test according to tension wood and opposite wood to determine DMOE. The results from the nondestructive test were compared with destructive tests namely three-point bending and compression parallel to grain where the samples were .prepared according to the British Standard. The DMOE was also compared with MOE and MOR obtained from three-point bending test using the non-destructive test's samples. Results showed that tension wood recorded greater DMOE mean values than opposite wood. A. mangium recorded higher DMOE in both tension and opposite wood followed by H brasiliensis and P. moluccana. Destructive tests also showed that A. mangium recorded the highest mean MOE and MaR III values followed by H brasiliensis and P. moluccana as determined by three-point bending test. Regression analyses showed that strong relationship were observed between DMOE and MOE detennined from non-destructive samples (ND samples) in both of tension (r= 0.92) and opposite wood (r2=0.79). However, DMOE and MOE obtained from British Standard samples (BS samples) were not correlated. In order for DMOE to be meaningful and able to predict MOE, correction factor has to be introduced to DMOE. Following inclusion of correction factor (CF), DMOE' was significantly correlated with MOE in A. mangium (R=0.80 and 0.88) and H brasiliensis (R=0.85 and 0.90) in tension and opposite wood, respectively. However, it did not successfully determined DMOE' in P. moluccana due to its low density that yielded large CF values. Between DMOE and MOR, only tension wood recorded good relationship (r2=0.70) compared to opposite wood (r2=0.46) in all species combined from ND samples. Anatomically, tension wood is characterized by thicker fibre wall, longer fibre, larger fibre diameter, smaller vessel diameter and small microfibril angle (MFA). The relationship between anatomical properties and mechanical properties showed that fibre wall thickness gave significant effect on DMOE in all individual species in both of tension and opposite wood. The fibre wall thickness significantly effect the MOE and MOR in all individual species in tension wood but only A. mangium and P. moluccana in opposite wood. For all species combined, fibre length was significantly correlated with DMOE, MOE and MOR in tension wood but only correlated to MOR in opp<?site wood. Ray height was significantly correlated with DMOE and MOE in opposite wood of the species studied. Fibre lumen diameter and fibre diameter were significantly correlated with MOE and MOR only in opposite wood. From the results, it can be concluded that the free-free flexural vibration method has the potential to predict the mechanical properties of the plantation species.